HUBUNGAN AKTIVITAS FISIK SERTA KONSUMSI SAYUR DAN BUAH DENGAN OBESITAS SELAMA PANDEMI COVID-19 PADA MAHASISWA UPN VETERAN JAKARTA TAHUN 2021 - Siti Nur Rahmawati (2021)
Obesity is one of the comorbid factors that increase the risk of COVID-19 transmission. A total of 12 COVID-19 patients (15.6%) with moderate obesity died within 30 days and as many as 8 COVID-19 patients (50.0%) with severe obesity died within 30 days. Obesity was significantly associated with an increased risk of death among COVID-19 patients (RR=1.42;95%CI=1.24-1.63). Preventing the risk of obesity, such as through activity and diet patterns, can suppress COVID-19 cases more optimally. The purpose of this study was to analyze the relationship between physical activity and consumption of vegetables and fruit with obesity during the COVID-19 pandemic among UPN Veterans Jakarta students. The study was conducted in March-July 2021. This research is a quantitative study using a cross sectional design with a chi square test. A sample of 397 was carried out by proportionate stratified random sampling. Based on the results of the study showed that 22.4% of students were obese. The results of the bivariate analysis showed a significant relationship between the duration and intensity of physical activity and Sedentary lifestyle (p-value 0.000). Then, there is no relationship between the frequency and the size of the portion of vegetable and fruit consumption (p-values 0.261 and 0.577). It is recommended that students do physical activity for at least 30 minutes/day and consume 400 grams of fruit and vegetables/day.